Effects of a recommended training device on developing rebound skill (attack-defense) of basketball players - Salama Saber, A. (World Journal of Sport Sciences, 2010)
Basketball is one of the leading sports activities, in general and specifically one of the leading team sports. It is a sport where defense is mixed with attack and the basketball player should play offensively and defensively as well. Training the attack/defense rebound skill is a burden for the coach as this particular skill is very difficult and so are its methods of training. The current study aims at identifying the effect of the recommended training device on developing the attack/defense rebound skill for basketball players. The researcher used the quasi-experimental approach on sample of 15 basketball players (under 18/20 years) of basketball team in Tanta Sports Club during the season 2009 - 2010. Results showed that the recommended training device enhanced the performance level of attack/defense rebounds and vertical jumps in basketball.